Diffractive photoproduction of dijets in ep collisions at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Jechow, M; Pavel, N; Molina, A; Antonelli, S; et al. (2008)
Diffractive photoproduction of dijets was measured with the ZEUS detector at the ep collider HERA using an integrated luminosity of 77.2 pb-1. The measurements were made in the kinematic range Q2 < 1 GeV 2, 0.20<y<0.85 and="" by="" diffractive="" energy,="" etjet="" etjet,="" exchange.="" fraction="" highest="" inelasticity="" is="" jets="" momentum="" of="" photon="" proton="" q2="" required="" satisfy="" taken="" the="" to="" transverse="" two="" virtuality,="" were="" where="" with="" xip="" xip<0.025,="" y="">7.5 and 6.5 GeV, respectively, and to lie in the pseudorapidity range -1.5<ηjet<1.5. Differential cross sections were compared to perturbative QCD calculations using available parameterisations of diffractive parton distributions of the proton. © 2008 Springer-Verlag / Società Italiana di Fisica.</y<0.85>